Social Return on Investment and Impact Reporting Transparency as Determinants of Investor Trust and Funding Sustainability in Foreign Architecture Development Companies in Bali - Putu Suda Nurjani; Sintia Permata Sari; Vinsensius Tibo (West Science Social and Humanities Studies, 2026)
The increasing complexity of global investment environments has encouraged development companies to demonstrate not only financial performance but also measurable social value creation and transparent accountability. Foreign architecture development companies operating in Bali face growing expectations from investors regarding sustainable development practices, social responsibility, and long-term investment credibility. This study aims to examine the influence of Social Return on Investment (SROI) and Transparency in Impact Reporting on Investor Trust and Funding Sustainability among foreign architecture development companies in Bali. This research employs a quantitative approach using a survey method involving 185 respondents consisting of investors, project managers, company representatives, and related stakeholders. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that Social Return on Investment has a positive and significant effect on Investor Trust, and Funding Sustainability. Transparency in Impact Reporting also significantly influences Investor Trust and Funding Sustainability. Furthermore, Investor Trust has a strong positive influence on Funding Sustainability. The mediation analysis confirms that Investor Trust plays an important mediating role in strengthening the relationship between sustainability-oriented practices and long-term funding continuity. These findings demonstrate that measurable social impact practices and transparent reporting mechanisms are essential strategic approaches for foreign architecture development companies to enhance investor confidence and maintain sustainable financial support. This study contributes to the literature on sustainable investment, stakeholder management, and corporate accountability by highlighting the importance of social value creation and transparency in strengthening investment relationships.